Analysis of Airport Taxis Vehicle Operating Costs at Tjilik Riwut Airport, Palangka Raya, Central Borneo - Chintia Evangelista; Robby Robby; Murniati Murniati (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
Vehicle operating costs refer to the costs associated with operating a vehicle for a given period of time. The PCI (Pacific Consultant International) method is the result of the sum of non-fixed costs and fixed costs. The purpose of this study is to determine the operational costs of airport taxi vehicles. When all primary data and secondary data have been collected, then further data analysis will be carried out using the PCI method. Based on the results of the analysis, it is known that the operational costs of sample 1 vehicles (Avanza 1.3 Transmover) are Rp. 4,226,- /km, sample 2 (Avanza 1.3 E M / T) is Rp. 4,606,- /km, sample 3 (Avanza 1.3 G M / T) is Rp. 4,595,- /km, and sample 4 (Veloz 1.3 M / T) is Rp. 3,969,- /km.